1968 Democratic State Convention program (1968)
This program outlines the agenda for the California Democratic State Convention and State Central Committee meeting held August 10–11, 1968, in Sacramento. It details committee meetings, registration times, caucuses, platform and credentials reports, and speeches by party leaders including Attorney General Thomas C. Lynch, Senate nominee Alan Cranston, and Senator Eugene McCarthy. The schedule includes the nomination and election of party officers, including the State Chairman and Women's Division Chairman. The final page lists officers of the Democratic State Central Committee, including Charles Warren as State Chairman and Jane Tolmach as Women's Chairman, South.